The Probability of Flare Occurrences Based on Sunspot Group and Magnetic Configurations - Dhani Herdiwijaya; Sherly Imelda (Jurnal Matematika & Sains, 2006)
We study the probability of flare occurrences observed in HÎ± and X-ray based on the classification and evolution of sunspot group and the magnetic structure within period 1994 to 2001. We found that there was a strong correlation between flare occurrences with the morphology and configuration of sunspot group and the magnetic structure. We also found that simple sunspot groups move more slowly before flare event, whereas complex groups move faster. On the other hand we did not find correlation between maximum area of sunspot group and the intensity of solar flare.